1989
DOI: 10.1002/jso.2930400105
|View full text |Cite
|
Sign up to set email alerts
|

Application of the immunoperoxidase method for rapid intraoperative pathological diagnosis of pancreatic cancer

Abstract: Intrapancreatic extension of pancreatic duct cell carcinoma in 19 resectable cases was evaluated by both hematoxylin and eosin (H&E) staining and quick immunostaining using antibodies against cancer-associated antigens--e.g., CA19-9, DUPAN 2, and CEA--on the intraoperative frozen-section biopsy during the course of laparotomy. By H&E staining, malignant lesions were identified in four of 19 cases (21%). By the immunostaining method, however, cancer cells were detected in 10 of 19 cases (52.6%). This immunostai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Six micrometerthick serial cryostat sections and the sections from the adjacent paraffin-embedded tissues were stained by H-E and the indirect immunoperoxidase method. The details of the cases were previously described [9].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six micrometerthick serial cryostat sections and the sections from the adjacent paraffin-embedded tissues were stained by H-E and the indirect immunoperoxidase method. The details of the cases were previously described [9].…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that gastrointestinal cancer-associated antigens (GICA), such as CA19-9, CEA, DUPAN 2, and CA-50, were also present but were restricted to the luminal side of the epithelial of the normal pancreatic duct. These antigens lose their normal localization patterns in connection with malignant changes of the cells and shed into the surrounding stroma [5-81. By taking this phenomenon into consideration, we developed a rapid immunostaining method based on this cancer-specific staining pattern of malignancy, coupled with conventional H-E staining, for intraoperative pathological examination [9]. It is a particularly useful method for defining cancer cells surrounded by dense fibrous connective tissue of the body and tail of the pancreas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without metastases no imaging technique can differentiate adenocarcinoma of the pancreas from other benign or malignant pancreatic masses.8 122223 Indeed, such differentiation may be extremely difficult during laparotomy even with the aid of histological and cytological examination, although rapid immunostaining of intraoperative biopsy specimens may be helpful. 24 A cytological diagnosis may be made from exfoliated cells in the duodenal secretions or pancreatic juice,232" from a fine needle aspirate of the pancreatic mass (taken percutaneously under ultrasonic, computed tomographic, or pancreatographic guidance or directly during operation),26-29 or from pancreatic ductal brushings at endoscopic retrograde cholangiopancreatography. 8 Biopsy specimens for histological diagnosis may be obtained at endoscopic retrograde cholangiopancreatography from a duodenum invaded by tumour, by a radiologically guided biopsy needle,30 or during surgery with or without intraoperative localisation by ultrasonography.…”
Section: From 2 Years Onwardsmentioning
confidence: 99%
“…The immunocytochemical method is useful for peritoneal washing cytology because of the difficulty in distinguishing adenocarcinoma from benign reactive mesothelial cells, and the detection of a small number of malignant cells [l-51, but due to its long reaction time, the method is not practical for intraoperative examination. We have reported an immunohistochemical staining pattern using anti-carcinoembryonic antigen (CEA) and anti-carbohydrate antigen in pancreatic carcinoma [6,7] and also developed a rapid immunoperoxidase staining method for intraoperative pathological diagnosis to determine the transection line for pancreatoduodenectomy [8,9]. In this report, we describe an improvement of the rapid immunostaining method using microwave irradiation and its application to the intraoperative cytological examination of pancreatic and biliary cancer.…”
Section: Introductionmentioning
confidence: 99%